2020
DOI: 10.3897/zookeys.963.53500
|View full text |Cite
|
Sign up to set email alerts
|

Catalogue, distribution, taxonomic notes, and conservation of the Western Palearctic endemic hunchback beetles (Tenebrionidae, Misolampus)

Abstract: Hunchback darkling beetles of the Ibero-Maghrebian genus Misolampus Latreille, 1807 (Tenebrionidae, Stenochiinae) encompass six species: M. gibbulus (Herbst, 1799), M. goudotii Guérin-Méneville, 1834, M. lusitanicus Brême, 1842, M. ramburii Brême, 1842, M. scabricollis Graells, 1849, and M. subglaber Rosenhauer, 1856. Previously known distribution ranges of the species were delineated using many old records, the persistence of such populations being questionable under the current situation of global biodiversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 91 publications
1
8
1
Order By: Relevance
“…The four selected bioclimatic variables for the ancestral state estimations showed a strong phylogenetic signal, particularly marked in the case of precipitation of driest quarter (BIO17) and mean temperature of wettest quarter (BIO8, Figure 4; Table 1). The recent history of isolation across populations with obvious patterns of morphological differentiation within M. gibbulus and M. goudotii (Rosas‐Ramos et al, 2020) were confirmed by our analyses. These species, characterized by high levels of intraspecific diversity, are distributed in the southwest of the Iberian Peninsula and in Morocco, regions previously identified as climatic refugia across a variety of taxa (Abellán & Svenning, 2014; Gutiérrez‐Rodríguez et al, 2017; Martínez‐Freiría et al, 2020; Miraldo et al, 2011; Sánchez‐Montes et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The four selected bioclimatic variables for the ancestral state estimations showed a strong phylogenetic signal, particularly marked in the case of precipitation of driest quarter (BIO17) and mean temperature of wettest quarter (BIO8, Figure 4; Table 1). The recent history of isolation across populations with obvious patterns of morphological differentiation within M. gibbulus and M. goudotii (Rosas‐Ramos et al, 2020) were confirmed by our analyses. These species, characterized by high levels of intraspecific diversity, are distributed in the southwest of the Iberian Peninsula and in Morocco, regions previously identified as climatic refugia across a variety of taxa (Abellán & Svenning, 2014; Gutiérrez‐Rodríguez et al, 2017; Martínez‐Freiría et al, 2020; Miraldo et al, 2011; Sánchez‐Montes et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, the north‐east of the peninsula would have been dominated by herbaceous vegetation, with small‐isolated areas within the regional steppic feature with local riparian forest (Jiménez‐Moreno et al, 2010). These past conditions and vegetation composition, together with the formation of the Ebro and Tagus Basins, provide clues for the current absence of Misolampus in the region, yet with favourable areas like Iberian Chain (Rosas‐Ramos et al, 2020). The southern area of the Iberian Peninsula was also characterized by herbaceous vegetation, even subdesertic flora implying dry and warm conditions, where mesothermic trees were probably in mid‐or high altitudes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During a series of field surveys conducted with the aim of analyzing the systematic position and conservation status of some species of Tenebrionoidea (López-Estrada et al 2019;Rosas-Ramos et al 2020), we observed a peculiar behavior in the endemic Iberian species Physomeloe corallifer (Germar, 1818). When handled, specimens of this taxon consistently extruded inner abdominal membranes from the proctodeal region (proctodeum: the embryonic posterior ectodermal part of the digestive tract, Merriam-Webster 2020; for a histological description of this region in a blister beetle, see Senarat et al 2014), which appeared intensely red or orange colored when the hemolymph is seen through them.…”
Section: Introductionmentioning
confidence: 98%